Analysis of the mental readiness of technology and engineering students before industrial work practice - Muliadi; Eddy Sutadji; Isnandar Isnandar; Widiyanti Widiyanti (Jurnal Inovasi Teknologi Pendidikan, 2025)
Industrial Work Practice is an important stage for Vocational High School students in applying the technical skills acquired during the learning process to the world of work. Internal readiness is a determining factor for students' success in facing industry challenges. This study aims to analyse the internal readiness of students at Lingsar State Vocational High School 1, majoring in technology and engineering, before participating in pre-school, and to identify factors that affect this readiness. The method used is a quantitative descriptive method; data are collected through interviews. Moreover, questionnaires showed that 84 students had high self-confidence, while 50 felt anxious due to a lack of technical skills, and 38 admitted they lacked sufficient industry experience. A total of 95 students assessed that practitioners' roles are critical in shaping their internal readiness, indicating that educators' mentoring has a significant influence on their readiness. Statistical analysis shows that perseverance and environmental support factors contribute to students' internal readiness. Soft skill training programs, work culture simulations and strengthening psychosocial support, to ensure students have optimal internal readiness before entering the workforce.